INFLECTION OF THE NATIONAL BROADBAND PROGRAM (PNBL) AND DEEPENING OF THE SOCIO-SPATIAL INEQUALITIES IN BRAZIL - Costa, Bruno Moreira Riani [UNESP]; Gallo, Fabricio [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2020)
In the present text we analyze the National Broadband Program (PNBL) and its trajectory. We can consider it the first major public policy aimed at the expansion of internet networks implemented after the privatization of the National Telecommunications System (SNT) in 1998. After the privatization of the SNT, there were also no solid and effective public policies and investments for sector coordination, leaving the private sector to selectively organize itself in Brazil according to its criteria, without any concern with the universalization of the service. Initially discussed in 2009, the PNBL was instituted by Decree in May 2010 and began its implementation the following year, ending in 2014. We seek to demonstrate how the distance between what was proposed and what was executed is due to an inflection of the Program, which from 2012 practically leaves direct public investment through the construction of the National Network and starts to be guided by the PNBL Special Tax Regime exemption policy, which, as we shall see, proved to be inefficient.
Keywords: Brazilian Territory; State; Public Policy; National Broadband Program